User preferences on long-acting pre-exposure prophylaxis for HIV prevention in Eastern and Southern Africa: a scoping review - Brian Pfau; Arden Saravis; Sarah N. Cox; Linxuan Wu; Rachel Wittenauer; Emily Callen; Cory Arrouzet; Monisha Sharma (BMC Public Health)
Abstract Background Novel formulations for pre-exposure prophylaxis (PrEP) such as injectables, implants, and intravaginal rings are emerging as long-acting alternatives to daily pills for the prevention of HIV. Eastern and Southern Africa (ESA) has the highest HIV burden as well as the highest PrEP coverage globally. To maximize uptake and population health benefits, it is crucial to understand the product preferences of potential users in ESA. Objective To conduct a scoping review focused on ESA to understand which PrEP products, particularly long-acting formulations, different subpopulations prefer and factors influencing preferences. Design We searched Pubmed, Embase, and conference abstracts using relevant search terms for studies conducted between 2014 and 2024. Studies were eligible for inclusion if they evaluated preferences for at least one long-acting or on-demand PrEP product among potential users in ESA. Results We identified 49 studies meeting eligibility criteria. Overall, most participants preferred longer-acting products over oral pills. On-demand PrEP was commonly preferred over daily dosing, and long-acting products were preferred over on-demand dosing. Most studies found injectables to be preferred over daily oral PrEP, implants, and rings, which was observed across subpopulations including men and women, youth, men who have sex with men, and female sex workers. Duration, efficacy, and discretion were the three most important factors influencing participants’ choices. Conclusions Long-acting PrEP products, particularly injectables, are preferred by a wide range of individuals in ESA over daily oral pills. Some subgroups preferred monthly oral PrEP or implants citing fear of injections, side effects and stigma-inducing injection marks, emphasizing the benefit of providing multiple products to maximize coverage. Strength and limitations of this study Some key populations, such as transgender women, were underrepresented in the literature. Most studies were published before long-acting products’ availability; therefore, they represent hypothetical stated preferences and not real-world uptake.